A systematic review and meta‐analysis of interventions to preserve insulin‐secreting β‐cell function in people newly diagnosed with type 1 diabetes: Results from intervention studies aimed at improving glucose control. Issue 1 (2nd November 2021) - Narendran, Parth; Tomlinson, Claire; Beese, Sophie; Sharma, Pawana; Harris, Isobel; Adriano, Ada; Maggs, Fiona; Burrows, Martin; Nirantharakumar, Krishnarajah; Thomas, Neil; Price, Malcolm J.; Andrews, Robert C.; et al.
Abstract: Aims: Type 1 diabetes is characterised by the destruction of pancreatic β‐cells. Significant levels of β‐cells remain at diagnosis. Preserving these cells improves glucose control and protects from long‐term complications. We undertook a systematic review and meta‐analyses of all randomised controlled trials (RCTs) of interventions to preserve β‐cell function in people newly diagnosed with type 1 diabetes. This paper reports the results of interventions for improving glucose control to assess whether they preserve β‐cell function. Methods: Searches for RCTs in MEDLINE, Embase, Cochrane CENTRAL, ClinicalTrials.gov and WHO International Clinical Trials Registry. Eligible studies included newly diagnosed patients with type 1 diabetes, any intervention to improve glucose control and at least 1 month of follow‐up. Data were extracted using a pre‐defined data‐extraction sheet with 10% of extractions checked by a second reviewer. Results: Twenty‐eight studies with 1662 participants were grouped by intervention into six subgroups (alternative insulins, subcutaneous and intravenous insulin delivery, intensive therapy, glucose sensing, adjuncts). Only three studies demonstrated an improvement in glucose control as well as β‐cell function. These interventions included intensive insulin therapy and use of an alternative insulin. Conclusions: This is the largest comprehensive review of RCTs in this area. It demonstrates a lack of robust evidence that interventions to improve glucose control preserve β‐cell function in new onset type 1 diabetes, although analysis was hampered by low‐quality evidence and inconsistent reporting of studies. Development of guidelines to support the design of trials in this field is a priority.